Preoperative Factors Associated with Weight Loss and Recurrent Weight Gain after Bariatric Surgery: A Longitudinal Study in a UK Public Healthcare Setting - Luqman Naim Bin Aizan; Akheel A. Syed; Bilal Alkhaffaf (Obesity Surgery, 2026)
Abstract Objective Bariatric surgery is an effective treatment for obesity. This study aims to identify demographic factors of weight loss and recurrent weight gain over a 10-year follow-up period. Methods This retrospective observational study includes 2092 patients for overall trends, 1032 patients for predictors of weight loss, and 605 patients for predictors of recurrent weight gain. Percentage total weight loss (%TWL) trends were measured over 10 years. The rate of weight loss and recurrent weight gain was used as a response variable in multivariate analysis. Results After bariatric surgery, mean ± SD %TWL was greatest at 31.3 ± 10.7 % by 2 years, followed by gradual recurrent weight gain to a %TWL of 25.1 ± 12.6 % at 10 years. Up to 5 years, %TWL was greater with Roux-en-Y gastric bypass (n=1080; 27.9 ± 11.5 %) and one-anastomosis gastric bypass (n=217; 28.3 ± 10.1) had greater %TWL than sleeve gastrectomy (n=795; 22.8 ± 12.5 %) (ANOVA, p < 0.005). Age, sex, preoperative body mass index, diabetes, operation type, and smoking were statistically significant predictors of weight loss up to 2 years (p < 0.05). Age, hypertension, Index of Multiple Deprivation quintile, and early %TWL up to 2 years were statistically significant predictors of recurrent weight gain after 2 years (p < 0.05). Conclusions Operation type, age, sex, preoperative body mass index, diabetes, operation type and smoking had significant associations with weight loss while age, hypertension, Index of Multiple Deprivation and initial postoperative weight loss had significant associations with recurrent weight gain.